(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, a radical improvement in the education sector has become a requirement of the time, many laws are adopted that regulate relations in the field of education, non-governmental educational institutions are created, the appearance of educational institutions is formalized. The material and technical base is changing and improving, funding for scientific research and social support is increasing, including increasing the income of the teaching staff, creating separate state structures in the direction of innovation, creating new departments in higher education institutions.